Shifting the Culture through Strategic Moves and Hires - Sarah Edwards (Academic Chairpersons Conference Proceedings, 2018)
Wondering how to motivate faculty to be the drivers for building and maintaining an assessment system that works? Join this session to consider how to make strategic moves and hires designed to have faculty own data and view assessment as a vital part of the faculty role.
Keywords: assessment; teacher education; strategic hiring